Desempenho agronômico da soja em função da adubação nitrogenada em diferentes estádios reprodutivos - Bahry, Carlos André (2011)
The use of additional nitrogen in soybean crop still brings many controversies in the scientific community about its real need for soybean agronomic performance. The aim of this work was to evaluate the soybean agronomic performance according to nitrogen fertilization in soybean, applied in nine growth stages with three different sources and four different doses of this nutrient. The test was carried out in UFSM/CESNORS, Frederico Westphalen. It was used three factor, doses x sources of nitrogen x time of application. The doses used were: 0; 30 kg.ha-1; 60 kg.ha-1; 90 kg.ha-1 and 120 kg.ha-1 of nitrogen, and sources: ammonium nitrate, calcium nitrite and amidic, applied in nine growth stages: R1; R3; R5.1; R5.2; R5.3; R5.4; R5.5; R6 and R7. The variables evaluated were: height of first pod, length of main branch, number of branches, length of branches, number of nods in the main branch, number of fertile nods in the main branch, number of nods in the branches, number of fertile nods in the branches, number of pods per plant, number of pods in the main branch, number of pods in the branches, number of pods per plant, and yield. The randomized blocks design was performed with three replicates. After variance analysis, the data was submitted to mean test. Duncan s 5% probability was used. The nitrogen application did not increase soybean yield in this work. Possibly by the median productivity, maybe the nitrogen fixation itself may supply the demand in this level. According these results we suggest new investigation, principal in precision farming areas.